Perceived Causes of Epilepsy from Society Perspective and its Relationship to Some Variables in Jordan (Journal of Namibian Studies : History Politics Culture, 2023)
The current study is aimed at knowing the perceived causes of epilepsy from the societal perspective and its relationship to some variables. The sample consisted of (320) participants; (65) males and (255) females. The measurement tool used in this study had sufficient reliability and validity to justify its use. The results of the study showed that the causes after birth came at the first rank with the highest average of (2.33), in contrast, myth and epilepsy came at the end, with a mean of (1.73), and perceived causes of epilepsy from the societal perspective as a whole was (2.04). Results: There is a superficial contradiction in the mean scores and standard deviations for perceived causes of epilepsy from the society’s perspective through diverse classes of variables for gender, age in addition educational qualification. Where the findings presented that there weren’t statistically significant differences (α=0.05) due to the effect of gender in all areas except for myth and epilepsy, and the differences came in favor of males. The results also showed that there were statistically significant differences (α = 0.05) due to the effect of age in all areas. There are statistically significant differences (α =0.05) due to the effect of educational qualification in all areas except for superstition and epilepsy.